Evaluation of inulin and aloe vera as green corrosion inhibitors for mild steel in 15% HCl - Ajayi, O.M; Everitt, N.M.; Voisey, K.T. (2016)
REACH legislation and PARCOM recommendations are driving research in environmental friendly alternatives to the highly toxic compounds currently used as corrosion inhibitors. Here two candidate plant extract green corrosion inhibitors are evaluated by direct comparison with commercially used corrosion inhibitors propargyl alcohol and 2-mercaptobenzimidazole. The two candidate green corrosion inhibitors are: 1. commercially available powdered inulin, extracted from Jerusalem artichoke; 2. aloe vera gel extracted directly from the plants. Immersion tests and weight loss measurements are used to determine the behaviour and inhibition efficiency as a function of concentration and temperatures of 20 ⁰C to 60 ⁰C for mild steel in 15% HCl. Results show that inulin and aloe vera act as corrosion inhibitors over the range of conditions used, the optimal concentration for both was 10%, compared to 0.4% for the commercial corrosion inhibitors. Inhibition efficiencies of up to 86% and 84% were observed for inulin and aloe vera respectively, compared to values of over 95% for the commercial corrosion inhibitors. There is some variation of behaviour for inulin and aloe vera with time and temperature.